2020
DOI: 10.3390/nu12103075
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nutritional Interventions in the Control of Musculoskeletal Pain: An Integrative Review

Abstract: Food consumption has significant positive effects on an individual’s health status, including the reduction of symptoms associated with musculoskeletal pain. However, specific food groups indicated for the treatment of pain are not yet determined. Hence, this review aimed to analyze the effects of nutritional interventions with specific diets, oils and/or fatty acids, and foodstuffs in natura in the reduction of musculoskeletal pain. An integrative review was conducted in the following databases: Embase, PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…In the same line, alterations in nociception and pain susceptibility were observed in the absence of weight gain (e.g. Song et al, 2017 ) indicating that the diet itself can have an impact – see for review ( Elma et al, 2020 , Mendonça et al, 2020 , Totsch et al, 2015 ). One study in mice even showed a positive association between HFD duration and longer recovery periods to basal pain thresholds after diet normalization ( Guillemot-Legris et al, 2018 ).…”
Section: Discussionmentioning
confidence: 92%
“…In the same line, alterations in nociception and pain susceptibility were observed in the absence of weight gain (e.g. Song et al, 2017 ) indicating that the diet itself can have an impact – see for review ( Elma et al, 2020 , Mendonça et al, 2020 , Totsch et al, 2015 ). One study in mice even showed a positive association between HFD duration and longer recovery periods to basal pain thresholds after diet normalization ( Guillemot-Legris et al, 2018 ).…”
Section: Discussionmentioning
confidence: 92%
“…In addition to fruit juices, particularly grapefruit juice known to inhibit CYP3A4 by reducing the metabolism of simvastatin, lovastatin and atorvastatin [14,15], tea flavanols can interfere with the pharmacokinetics of drugs in humans, by interaction with CYP3A4 and with phase III transporters of the drug detoxifying system, mainly the multidrug resistance 1 (MDR1) [51], OAT [17,51], and organic cation transporters (OCT) [51]. However, the consumption of fruits and vegetables [52,53], rich in antioxidant flavonoids, as well as Med-D and physical activity [53], can reduce musculoskeletal pain. Med-D can reduce chronic pain [54], and a high adherence to the Med-D was associated with pain improvement in older adults recruited in the Seniors-ENRICA-1 and Seniors-ENRICA-2 cohorts [55].…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional interventions may have effects in reducing chronic musculoskeletal pain, reducing comorbidities—such as obesity and cardiovascular diseases—and, thus, reducing health costs [ 10 , 11 ]. It is important to highlight that there is a lack of research on the effectiveness of diet therapy for people with chronic pain, and on the barriers to its implementation in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the daily consumption of certain foods—such as fruits, vegetables, yogurt, red wine, and extra-virgin olive oil—can modulate pain [ 9 , 10 , 11 ]. Many of these food items are included in the traditional Brazilian diet (DieTBra), such as rice, beans, fruits, and vegetables [ 12 ].…”
Section: Introductionmentioning
confidence: 99%